Consecuencias en la autoestima de mujeres víctimas de violencia de género de la Fundación Karina Miranda de la ciudad de Quevedo - Rodriguez Honores, Emily Domenica (2024)
Throughout history, women have faced constant challenges in their pursuit of better living conditions and the development of their professional careers. Women who are victims of violence experience a significant decrease in their self-esteem, leading to feelings of frustration, failure, and devaluation in society. Furthermore, it has been observed that as physical, psychological, sexual, and economic violence increases, the self-esteem of these women tends to decrease. This phenomenon highlights the importance of addressing the impact of gender-based violence on women's self-esteem and emotional well-being. This quantitative research study focuses on the repercussions of gender-based violence on the self-esteem of the victims, with the main objective being to identify and analyze the connections between self-esteem and gender-based violence in order to fully understand the impact that the latter has on self-esteem. Based on these findings, the design of a workshop aimed at promoting healthy self-esteem in the context of gender-based violence is proposed. The methodology used in this quantitative study allowed for the collection and analysis of data to identify the degree of impact on the self-esteem of women who are victims of gender-based violence. The sample consisted of 42 women affiliated with the Karina Mirando Foundation in the city of Quevedo, where the focus of the study was on gender-based violence and its impact on self-esteem. To achieve the research objectives, relevant bibliographic sources were consulted to address the variables under consideration. As data collection instruments, the Type and Phase Assessment Scale (EETFVG) was used to identify the presence of gender-based violence, as well as Rosenberg's Self-Esteem Scale to measure the level of self-esteem among the participating women.